INSTRUMENTS TO EVALUATE QUALITY AND SAFETY IN THE SURGICAL CENTER - AN INTEGRATIVE REVIEW - José Augusto Pereira Gomes; Maria Manuela Martins; Carla Sílvia Neves da Nova Fernandes (Universidade Federal do Paraná, 2016)
This study aimed to identify the instruments in existence for evaluating quality in the surgical center. An integrative review was undertaken of the literature in the period 2010 - 2015 through the use of specific search engines. Following analysis in accordance with the inclusion criteria established, 13 articles were selected. The analysis of the scientific evidence obtained made it possible to organize the results in three thematic areas: evaluation of the structure, evaluation of the process, and evaluation of the result. The instruments analyzed are more frequent in the ambit of the process and associated with the patient safety culture. The results reveal the need for further development at this level specifically through the construction and validation of instruments which are more broad-ranging, integrating the different components of the assessment of quality.